Paying for the Selected Son: Sex Imbalance and Marriage Payments in China - Yuanwei Xu (ZBW - Leibniz Information Centre for Economics, 2021)
This paper shows that the rising male surplus has strengthened marriage distortions in China by causing an increase in brideprice payments. The identification relies on comparison between siblings from the same natal family who are born in different birth years and thus exposed to various demographic structures. I find robust evidence that a rise in male-female sex ratios significantly increases the incidence and value of brideprices, but has no influence on dowries. Such a positive effect on brideprices is found predominantly in natal families characterized by low education, fewer number of children, and with more daughters than sons. Further investigations show that dowries carry a strong intergenerational function for help and care in parents' old age but brideprices do not. In addition, dowries are positively associated with female bargaining power. This paper provides the first empirical evidence showing that demographic imbalance causes marriage distortion with rising brideprices, and suggests that brideprices and dowries carry different significance in the Chinese society.
Keywords: J12; J13; J16; P21; 330; Sex Imbalance; Brideprices; Dowries; Marriage Payments; China